Sambalicious Meletop / Che Muhammad Nazrin Che Mohd Nor - Che Mohd Nor, Che Muhammad Nazrin (2019)
Sambalicious Meletop is a business that carries out online business for food product. This product consist of anchovies, tempe, crispy fried shallots and ground nuts with quality product used and special ingredients without additional chemical or powder. This business created top rovide an opportunity to all customers who have problem in appetite. It is because sambalicios can give us more appetite when we eat with a hot rice as an additional menu. What is the special about this product is this is homemade with quality product and got certificate Halal from Jakim and also the price is affordable. So, we focus to customer jn Kuala Lumpur and Selangor and we also have a postage service to customer outside from Lembah Klang. Retaining Sambalicious Meletop's customers is a very strong suit for this business, so we our own strategies to ensure that our customers satisfied with our services.